2006
DOI: 10.1021/cm061085r
|View full text |Cite
|
Sign up to set email alerts
|

Bi2ZnTiO6:  A Lead-Free Closed-Shell Polar Perovskite with a Calculated Ionic Polarization of 150 μC cm-2

Abstract: Bi2ZnTiO6, a lead-free analogue of PbTiO3, has been prepared by high-pressure solid-state synthesis methods. Structural analysis reveals that the tetragonal distortion (c/a ratio = 1.21) of Bi2ZnTiO6 is the largest reported for any d0 B site Pb or Bi based perovskite. Significant cation displacements result in a point-charge calculated polarization of 150 μC cm-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
166
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 19 publications
8
166
2
Order By: Relevance
“…The perovskite phase is rather formed only when the synthesis is carried out at high pressures (5)(6) and high temperatures (~ 1000 o C) [8][9][10]. However, for the sake of convenience, we may treat Bi(M M )O3 as a virtual compound which can form solid solution with other real perovskite compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The perovskite phase is rather formed only when the synthesis is carried out at high pressures (5)(6) and high temperatures (~ 1000 o C) [8][9][10]. However, for the sake of convenience, we may treat Bi(M M )O3 as a virtual compound which can form solid solution with other real perovskite compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuthbased ceramics such as Bi 1/2 Na 1/2 TiO 3 (BNT) and Bi 1/2 K 1/2 TiO 3 (BKT) denote promising starting points because of the resemblance of the Bi 3þ ion with the Pb 2þ ion in terms of electronic configuration, i.e., a 6s 2 lone-pair configuration. [12][13][14][15] As BNT requires high switching fields and BKT is hard to fully densify by conventional sintering techniques, solid solutions of these materials were investigated. 16,17 It was found that compositions at the morphotropic phase boundary (MPB) of (1Àx)BNT-xBaTiO 3 ((1Àx)BNT-xBT, with x ¼ 0.06 $ 0.07) and (1Àx)BNT-xBKT (with x ¼ 0.16$0.2) offer enhanced electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] On the other hand, tetragonal Bi͑Zn 0.5 Ti 0.5 ͒O 3 ͑BZT͒ has been reported to have very high c/a ratio of 1.21 and large calculated ferroelectric polarization of 150 C / cm 2 , whereas it is not stable in its pure form and can only be stabilized at high pressure. 10 However, it is reported that BZT-containing solid solutions can be stable in atmospheric condition and still have enhanced c/a ratio, ferroelectric polarization, and increased T c . [11][12][13][14] At present, reports on BZTcontaining piezoceramics are mainly focused on the solid solution of tetragonal BZT with other lead-containing tetragonal perovskites such as PbTiO 3 .…”
Section: Introductionmentioning
confidence: 99%